The study on expanded austenite formation of duplex stainless steels treated by low temperature carburizing in a tube furnace atmosphere / Nor Farhana Mohd Yusof - Mohd Yusof, Nor Farhana (2012)
Duplex stainless steels (DSS) are a class of technologically important materials widely used in various sectors of industry. The problem associated with the poor tribological properties of these materials has recently been tackled by many investigators. Surface engineering has proven to be a useful method for increasing the hardness and wear resistance of stainless steel without compromising their corrosion resistance. Low temperature thermochemical carburizing technique has been developed thicker hardened layer on the surface of duplex stainless steels to achieve combined improvement in hardness and wear resistance. The resultant carburized layer is free from chromium carbide precipitates and contains with austenite phase supersaturated with carbon. An attempt was conducted in various process parameters by adding 3 - 5% CH4 and mix N2 with in tube furnace atmosphere at temperature 450°C, 500°C and 550°C for 7 h and 14h. Structure and properties of the carburized layer were investigated by various tests such as X-ray diffraction (XRD), scanning electron microscopy (SEM), optical microscope and testing for microhardness and wear to reveal the character of produces thin layers. The surface hardness and wear resistance of the carburized layer was significantly increased compared to untreated one. The carburized layer is contains with austenite phase supersaturated with carbon and free from chromium carbide precipitates. However, by increasing treatment temperature until 550°C with 5% CH4 , it can lead to the formation of chromium carbide precipitates in the carbon enriched layer, and thus deteriorate the quality of the specimens in terms on corrosion resistance. The carburizing treatment produced thicker and harder layer at 14 h compared to 7h treatment; the maximum hardness was about 703.0HV0.o2s compare to untreated DSS at 212.5HVo.025· The carburizing treatment specimens gave high wear resistance which corresponded to high hardness values. Therefore, in this study it can be concluded that these two parameters have a main role in producing expanded austenite and chromium nitride. The potential application for this carburized surface treatment on DSS may use for piping and fitting parts in chemical and petrochemical where improvement in hardness and wear resistance.